The Use of STAD Model in Teaching English - Ingriyani Y Rawung (Sintuwu Maroso Journal of English Teaching, 2017)
The research aims to describe the use of Students Team Achievement Division as a cooperative learning model in teaching English to students of SMPN 2 Poso. The subject this research was the eighth grade students at SMPN 2 Poso. Data were collected by observation, interview, documentation and questionnaire. The findings show that the English teacher of SMPN 2 Poso applied STAD model consists of five steps in teaching English.Keywords: student teams achievement, model, teaching English